A comparison between the sensitivities of VLC receivers containing an off-the-shelf SPAD array and an APD - Zhang, L; Chun, H; Faulkner, G; O'Brien, D; Collins, S (IEEE, 2017)
This paper proposes a method to detect photon counts from a commercial off-the-shelf SPAD array. Experiments show that using this method the sensitivity of a VLC receiver that incorporates this SPAD array approaches the limit set by Poisson noise.